2009
DOI: 10.1002/jcp.21977
|View full text |Cite
|
Sign up to set email alerts
|

Zyxin controls migration in epithelial–mesenchymal transition by mediating actin‐membrane linkages at cell–cell junctions

Abstract: Development is punctuated by morphogenetic rearrangements of epithelial tissues, including detachment of motile cells during epithelial-mesenchymal transition (EMT). Dramatic actin rearrangements occur as cell-cell junctions are dismantled and cells become independently motile during EMT. Characterizing dynamic actin rearrangements and identifying actin machinery driving these rearrangements is essential for understanding basic mechanisms of cell-cell junction remodeling. Using immunofluorescence and live cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
(66 reference statements)
2
40
0
Order By: Relevance
“…Actin becomes highly decorated with non-muscle myosin II during the reorganization of actin into transcellular networks and obvious deformations are visible at points where these cables abut cell-cell junctions. 9 It is also at this point where cell spreading reverses and cells revert to having a smaller 'footprint' on the culture surface. Consistent with a role for myosin contractility in this process, changes in myosin phosphorylation are observed during epithelial scattering of MDCK cells; phosphorylation is reduced in early scattering, when spreading is observed, and increases in late scattering, when cell compaction, migration, and detachment occur.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Actin becomes highly decorated with non-muscle myosin II during the reorganization of actin into transcellular networks and obvious deformations are visible at points where these cables abut cell-cell junctions. 9 It is also at this point where cell spreading reverses and cells revert to having a smaller 'footprint' on the culture surface. Consistent with a role for myosin contractility in this process, changes in myosin phosphorylation are observed during epithelial scattering of MDCK cells; phosphorylation is reduced in early scattering, when spreading is observed, and increases in late scattering, when cell compaction, migration, and detachment occur.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] HGF stimulation of MDCK cells results in a dramatic change in cell morphology and cell behavior that ultimately results in cells wrenching apart their cell-cell adhesions in dramatic fashion and 'scattering' about the culture surface. 3,8,9 Cellular imaging, summarized in Figure 1, has shown that scattering is accompanied by a transient cell spreading phase, with cells increasing spreading on the culture surface by roughly double. The spreading phase is immediately followed by compaction of cells as spreading is reduced, an increase in cell migration, and disruption of cell-cell adhesions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations